Antifungal Potential of Cell-Free Supernatant Produced by Keratinolytic Fungi against Ganoderma boninense (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Keratinolytic is a microorganism ability to degrade keratin substrates. Fungi are known to produce the enzyme keratinase. This research was carried out aiming to know the keratinolytic fungi potential in inhibiting Ganoderma boninense fungi. Five isolates of keratinolytic fungi coded A 31, A 18, A 12, K 18, and A 29 have antagonistic ability against G. boninense. A 12 and A 18 had the largest inhibitory diameter of 25.23 mm and 24 mm, respectively, after 7 days of incubation. The ability of A 12 and A 18 antagonisms was observed by testing the supernatant of keratinolytic fungi incubated in a feather meal broth medium. An 18 has the largest antagonism percentage of inhibition at 84.72% against G. boninense, followed by A12 (77.78%) and combination treatment of A 12 + A 18 (73.55%) after 7 days of incubation. Keratinolytic fungi can also grow on minimum salt chitin medium (MSCM) and produced a hydrolysis zone after 3 days of incubation. G. boninense hyphae abnormalities were observed by using a 100x magnification microscope. Moreover, hyphae lysis and dwarf, curved, rolled, and curly hyphae were also observed after giving treatment on A 12, A 18, and the combination treatment of both isolates. These results showed that both keratinolytic fungi isolates and the supernatant are powerful biocontrol agents against G. boninense. There is no previous research report on endophytic fungi inhibiting the growth of Ganoderma boninense. In the future, keratinolytic fungi can be applied in agriculture technology.